Catálogo de la vegetación en jardines domésticos de Bogotá, Colombia (2014)
Urban domestic gardens contain an important diversity of plants, which provide habitat and food for the animals that live in cities. In order to recognize the diversity of plants in domestic gardens of Bogotá, D.C., seven localities that represent the city landscape diversity were selected. In each locality we inventoried the plant diversity of ten houses. 4110 individuals, 238 species (grasses, shrubs, trees, vines and epiphytes) and 85 families were recorded. A list and a photo catalogue with all species is provided for the first time.